Eksplorasi Desain TPACK dalam Pengembangan Smart Hydroponic System Berbasis IoT sebagai Media Peningkatan Kemampuan STEM Siswa - Nove Kurniati Sari; Zulhafandi Zulhafandi; Banyuriatiga Banyuriatiga; Syaddam Syaddam (Fakultas Teknologi Informasi, 2026)
STEM education is an interdisciplinary approach that integrates various disciplines to equip Students to face the challenges of the digital era and the Industrial Revolution 4.0. The success of this innovative learning implementation depends on how a teacher designs a cohesive instructional scenario. In designing STEM learning that integrates the latest technology, Teachers need specific competencies outlined in the TPACK framework. The purpose of this research is to develop a learning design model based on the TPACK framework that integrates STEM approaches via IoT instruments, using a case study of the Smart Hydroponic System project, to hone Students' computational thinking logic using block code. In the research method employed, qualitative descriptive and experimental technical approaches with exploratory characteristics are used. This study succeeded in formulating seven elements of TPACK to convert complex STEM materials into